Optimalisasi Pembelajaran Digital bagi Guru di Madrasah Aliyah Al-Mutmainnah Leseng - Wiwi Noviati; Eryuni Ramdhayani; Sri Nurul Walidain; Rini Qurratul Aini; Riadi Suhendra (Indonesian Publication Center, 2026)
The rapid development of digital technology requires teachers to have adequate digital competencies to support innovative and effective learning. However, teachers at Madrasah Aliyah Al-Mutmainnah Leseng still face challenges in utilizing digital learning platforms, developing digital teaching materials, and integrating technology into classroom learning. This community service program aims to improve teachers' digital competency through training and mentoring on Augmented Reality (AR) and Artificial Intelligence (AI). This program involved 25 teachers and was implemented in three stages: preparation, implementation, and evaluation. The implementation phase consisted of training and practical mentoring in developing AR-based learning media and utilizing AI to support learning administration, including the development of teaching modules, learning materials, and assessment instruments. Evaluation results showed an increase in participants' understanding and skills in utilizing digital technology. Teachers successfully developed AR-based learning media and demonstrated the ability to use AI-based platforms to improve lesson planning and administrative efficiency. Furthermore, participants demonstrated increased confidence in integrating digital technology into teaching and learning activities. Overall, this program positively contributed to strengthening teachers' digital competency and supported the implementation of more innovative, interactive, and technology-based learning practices.